Experimental and Numerical Study of the Drying Process of a Consolidated Clay Soil - Wen-Qing Cheng; Han-B ing Bian; Qian-Feng Gao; Mahdia Hattab (Advances in Civil Engineering)
The clay soil is composed of solid skeleton and porous and can be studied in the framework of porous media. During the drying process, the initial saturated clay soil deforms mainly due to the changes of water content and capillary pressure. With the further increase in capillary pressure, the soil cracks. In fact, the deformation and the stress in clay soil are tightly related with the water content and capillary pressure. Therefore, it is of great interest to understand the changes in capillary pressure and water content within the clay soil during the drying process. However, it is difficult to obtain these field variables by experiments alone. Therefore, the numerical simulation could be good choice for deeper understanding of the dry process in clay soil. In current research, the combined numerical simulation and laboratory experiments research are conducted; the numerical results are compared with the laboratory observation. This research is the basis for the further study of the cracking process of clay soil due to drying.